Implementasi Teknik Token Economy dalam Mengubah Perilaku Maladaptive pada Anak Usia Dini - Ridha Maghfirah; Endang Setyaningsih (Jurnal Ilmu Sosial dan Humaniora, 2026)
Maladaptive behavior in early childhood can hinder learning processes and social development, necessitating appropriate behavior modification strategies. One applicable technique is the token economy, which involves providing positive reinforcement in the form of tokens that can be exchanged for rewards. This study aims to describe the implementation of the token economy technique in modifying maladaptive behavior in young children. A qualitative approach using a case study method was employed. Data were collected through interviews and observations involving a five-year-old child, the class teacher, and the parents, and were subsequently analyzed using thematic analysis. The results indicate that prior to the implementation of the token economy, the subject frequently struggled to follow instructions, left their seat without permission, and disturbed peers during lessons. Following the consistent application of the technique, the subject demonstrated behavioral changes, such as greater adherence to rules, the ability to complete tasks, a reduction in disruptive behavior toward peers, and an improved ability to wait for their turn. The study demonstrates that the token economy technique is effective in helping to reduce maladaptive behaviors and enhance adaptive behaviors in young children.